The evaluation of physical fitness improvement after 8 weeks individual strength and conditioning program on B1 Turkish national football team - Biyikli, T.; Güler, U.; Albayrak Kuruoglu, Y.; Akgül, E.; Çetinkaya, S.; Boyaci, A. (European Journal of Physical Education and Sport Science, 2018)
This study aims to evaluate the physical fitness improvement after 8 weeks individual strength and conditioning program on B1 Turkish National Football Team, to reveal their motoric differences and to identify strengths and weaknesses of athletes. 11 male athletes (age ranging between 25,09 ± 3,53) in B1 Turkish National Football Team have participated in this study. Out of these athletes, 9 of whom account for B1 visually impaired football players (footballer) and 2 of whom account for a goalkeeper with no disability. Vertical jump, kneel down health ball throwing, sitting and reaching, 20 m speed, auditory reaction, grip strength, right-left had, pro-agility, anaerobic strength and cooper measurements have been applied with the interval of 8 weeks as pre-test and post-test. All statistical analyses have been conducted by using SPSS 13.0 packet program. While a significant difference has been found in 0.05 level in speed, agility, anaerobic strength and maximal oxygen capacity of the B1 football national team (p<0,05), no significant difference has been found out although there is an average improvement between pre-test and post-test in other variables. (p>0,05). No significant difference has been found out between pre-test and post-test statistical values of the variables applied to B1 football national team goalkeepers. (p>0,05). As a result, an improvement in positive level has been observed in overall performance parameters of B1 football national team athletes and individual strength and condition training prepared according to 8 weeks pre-test results. Raising interest of B1 football national team goalkeepers to the training and creating a competitive environment could prove useful in increasing overall performance levels